2021
DOI: 10.1097/md.0000000000024680
|View full text |Cite|
|
Sign up to set email alerts
|

Platelet-rich plasma injection vs corticosteroid injection for conservative treatment of rotator cuff lesions

Abstract: Background: To explore the effectiveness of platelet-rich plasma (PRP) injection regarding functional recovery, pain relief, and range of motion (ROM) of shoulder compared with the corticosteroid injection in patients with rotator cuff lesions treated non-operatively. Methods: An electronic literature search was performed by 2 authors in the PubMed, Embase, Cochrane Library, and Web of Science databases to identify relevant randomized controlled trial (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…21 The finding in our sample that the majority of outcomes were negative for PRP in the treatment of rotator cuff lesions, Achilles tendinopathy, and fractures is also in line with lack of current evidence for these PRP uses. 75,83,102 Finally, although there were no clinical studies on PRP for plantar fasciitis within our top 50 most cited articles, it should be noted that there is emerging evidence of greater efficacy for PRP compared with corticosteroids. 42 However, the overall consensus continues to state that PRP is currently an experimental therapy and thus requires proper patient education regarding risks and benefits.…”
Section: Discussionmentioning
confidence: 97%
“…21 The finding in our sample that the majority of outcomes were negative for PRP in the treatment of rotator cuff lesions, Achilles tendinopathy, and fractures is also in line with lack of current evidence for these PRP uses. 75,83,102 Finally, although there were no clinical studies on PRP for plantar fasciitis within our top 50 most cited articles, it should be noted that there is emerging evidence of greater efficacy for PRP compared with corticosteroids. 42 However, the overall consensus continues to state that PRP is currently an experimental therapy and thus requires proper patient education regarding risks and benefits.…”
Section: Discussionmentioning
confidence: 97%
“…These findings are consistent with other studies [ 60 , 79 ]. Different systematic reviews have shown that steroid injection had a quick recovery in reducing the symptoms than PRP, which has a slower improvement but long-term permanent effect [ 50 , 80 ]. Yang et al, 2017 found that the PRP is better than steroid injection for long-term pain reduction in plantar fasciitis, but there was no noticeable observed field difference between short- and intermediate-term effects [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…It needs six to eight weeks for full activities after injection [82]. Steroids lack this property and interrupt the inflammatory and immune cascade, which is short-lived [80,83]. Ang et al, 2019 found in the context of lateral epicondylitis that corticosteroid relieves acute pain but not in the long term, which may be due to the short half-life of the steroid [37].…”
Section: Discussionmentioning
confidence: 99%
“…38 According to the American Academy of Orthopedic Surgeons (AAOS), a single CS injection with a local anesthetic provides short-term pain relief as well as improved shoulder joint function. 39 A systematic review 40 reported that CS injections for the management of shoulder impingement yielded less pain at 6 weeks follow-up but not at T A B L E 5 Mean difference of functional and pain scores between corticosteroid and platelet-rich plasma treatment A previous meta-analysis 7 demonstrated that CS yielded shortterm pain relief as well as better functionality in comparison to PRP, which is in line with our findings, but the results were only reported as being statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…6 As a consequence, alternative treatment methods are being considered. 7 One of these is platelet-rich plasma (PRP).…”
Section: Introductionmentioning
confidence: 99%